PERILAKU MASYARAKAT & ETIKA MEDIA DALAM TAYANGAN INFOTAINMENT DI TELEVISI - Nugroho, Puji (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
ABSTRACTThe proliferation of infotainment shows on television media for current decades is considered quite disturbing for broadcasting stakeholders in this country. The mass media through its four functions should be able to perform these functions in sequence and the four should run proporsonally, either the functions of educating, providing information, entertaining and influencing. But along with the disowning of conscience by media owners who are very oriented to the political economic of the liberal media, the main purpose of broadcasting is merely pursuing for ratings to be able to reap a lot of advertisements, with the reason people as the owner of the sovereign broadcasting like it. The orientation of media owners through infotainment shows that sold well consumed by society, on one hand, potentially damage the morality of the society into an opportunistic, apathy and hedonist nation. The situation of upheaval domestic political is also considered to foster infotainment shows in the midst of people's worries about the increasingly uncertain political situation, especially the corruption news that has filled the labyrinth of society, more saturated, so that people seek entertainment on television through infotainment shows.The lack of favor towards the conscience and the morality of society, thereby crashing into the corridor of mass media function, encourages media owners to tend to display something of added value in society, by denying the educational function, providing useful information and influencing the society with more cosmopolitan thinking. This is the serious problem faced by this nation, and has not obtained law enforcement as regulated in legislation. In this case, the Indonesian Broadcasting Commission which has repeatedly reprimanded and gave strong warnings against television stations that broadcast infotainment shows inappropriately, merely to rebuke and commemorate, without being able to bring it into the realm of justice. The inherent strength of capital accompanied by the social political power of the media owners, have made all violations and crimes in the mass media unfolded without ever being touched by the law. Keywords: People behavior, media ethics and infotainment shows on television